Do Students’ really understand ‘Newton Laws of Motion’? - Shweta Singh 23 S.B. Bhattacharya (Education India Journal: A Quarterly Refereed Journal of Dialogues on Education, 2015)
Newton laws of motion is a very important and fundamental topic taught at secondary and higher secondary level as they have easily visible applications in the daily lives of students.Present study is an attempt to assess higher secondary students’ understanding of newton laws of motion by using a two-tier physics concept achievement test (PCAT). The sample consists of 480 XI th grade studentsfrom selected schools of Haldwani city in Uttarakhand. The finding of the study shows that students have an average level of concept achievement in newton laws of motion. Present study also reveals that gender differences do exist in concept achievement of newton laws of motion, with boys outperforming girls in PCAT.